Bullying di Kalangan Mahasiswa Pada Perguruan Tinggi di Indonesia: Bimbingan dan Konseling sebagai Solusi - Ahmad Putra; Muhammad Abil Wahyuda; Yulia Fitria (Counselle| Journal of Islamic Guidance and Counseling, 2025)
This paper is motivated by the rise of bullying among students in recent months that has appeared on social media and occurred in several national universities. This issue went viral because it happened not once or twice, but often surfaced which ultimately raised questions about the resolution of this bullying case. In this paper, the author will describe a series of several cases that occurred in 2025 and in previous years experienced by students at several national campuses and the resolution process that can be done from the scientific side of guidance and counseling and the role of BK study program lecturers in resolving the problem of bullying in higher education. The method used by the author in this research is library research, where the author searches and finds research materials through various sources, including books, journals and other accurate sources. The results of this study found that: first, bullying has occurred a lot in higher education, especially among students, second, bullying against students also involves lecturers, third, BK lecturers play a very important role in resolving the problem of bullying among students by utilizing services available in BK, such as individual counseling services, information services, consultation services, and group guidance services. It is hoped that this service can be utilized by all BK lecturers and the academic community to resolve bullying among students.